REPRESENTASI KEKECEWAAN PEREMPUAN PADA CERPEN “PEREMPUAN YANG MENIKMATI TUBUHNYA SENDIRI” KARYA M. RIFDAL AIS ANNAFIS - Sucipto, Hanna Aulia Rahmah; Nabila, Jihan; Vinindika, Nabila; Nugraha, Robby; Harini, Yostiani Noor Asmi (UNIB Press, 2024)
This study aims to describe the representation of women's disappointment in the structure of short story texts. The theories used in this study are structural theory by Levi-Strauss and literary sociological theory by Damono with the originator of Ian Watt's theory. This study uses qualitative descriptive method by analyzing the relationship between short stories and social reality. The short story